Hubungan Culture Shock dengan Kesulitan Belajar Pada Siswa Kelas X SMK Negeri 8 Surakarta - Desyan Bagaskara, Muhammad; Hera Heru Sri Suryanti; Ahmad Jawandi (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The purpose of this study was to identify and analyze the correlation between cultureshock and learning difficulties at the tenth-grade students of SMKN 8 Surakarta in 2023/2024academic year, to analyze the correlation between culture shock and students' learningdifficulties, to provide recommendations for school in overcoming culture shock and learningdifficulties faced by students. The research data were collected using a questionnairedistribution that was divided into two, namely a questionnaire about culture shock and aquestionnaire about learning difficulties. Data analysis in the study was carried out usingcorrelational techniques to determine the strength of the relationship between the two variables. The results of the study showed that there was a significant relationship between culture shockand students' learning difficulties. The higher the level of culture shock faced by students, thehigher the learning difficulties experienced by them. Based on the results of the study, it couldbe explained that "there is a correlation between culture shock and learning difficulties ofstudents in class X of SMKN 8 Surakarta in the 2023/2024 academic year." This was by knowingthe r-count was 0.513. With a value of N = 30, the r-table value with a significance of 5% was0.361 and 1% was 0.463. So, the conclusion was that the r- count is greater than the r-table witha significance level of 5% and 1% or 0.361 <0.513> 0.463. This finding indicated the importance ofspecial attention to the impact of culture shock in the teaching and learning process.